2020
DOI: 10.1177/0284185120966724
|View full text |Cite
|
Sign up to set email alerts
|

The mean bilateral proximal extension of the clot is associated with pulmonary embolism severity parameters and management-associated outcomes

Abstract: Background The value of the proximal extension of the clot in risk stratification of pulmonary embolism (PE) has not been established. The mean bilateral proximal extension of the clot (MBPEC) is a computed tomography (CT) radiological score, where initial evaluation showed promising results considering its ability in predicting the severity of PE. Purpose To explore the possible associations between MBPEC and PE-severity parameters, short- and long-term outcomes of PE, and inter-observer agreement. Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although our results indicate that the extent of PE should not be given decisive clinical importance in the risk stratification following PE, we have previously shown an association between Troponin elevation in acute PE and MPBEC score. 24,25 This indicates that MBPEC might be relevant in contexts other than mortality. Furthermore, there may be clot parameters other than total clot volume/burden that may be important to assess, such as semi-quantitative clot burden measurement, clot volume quantification and lung perfusion quantification using iodine maps, signs of chronicity, as those accurately predict chronic thromboembolic pulmonary hypertension (CTEPH) and other post-PE sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our results indicate that the extent of PE should not be given decisive clinical importance in the risk stratification following PE, we have previously shown an association between Troponin elevation in acute PE and MPBEC score. 24,25 This indicates that MBPEC might be relevant in contexts other than mortality. Furthermore, there may be clot parameters other than total clot volume/burden that may be important to assess, such as semi-quantitative clot burden measurement, clot volume quantification and lung perfusion quantification using iodine maps, signs of chronicity, as those accurately predict chronic thromboembolic pulmonary hypertension (CTEPH) and other post-PE sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study has demonstrated excellent MBPEC score inter-rater agreement. 25 Qanadli or Mastora scores were not assessed, hindering a comparison between MBPEC and a reference standard score. However, excellent correlation between the Qanadli score and MBPEC score has previously been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central clot location can be of value as a prognostic marker for rapid risk stratification of PE. In contrast to obstruction scores, the classification of PE according to its most proximal level is frequently included in radiology reports and easier to understand by the physician (24,25) . In agreement with multiple studies and meta-analyses (19&25) , our study demonstrated that clinical prognosis in patients with PE is significantly influenced by PE location, and large proximal pulmonary emboli are expected to have more serious consequences (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of RVD qualitative findings between study outcome groups showed significant differences in leftward bowing of the interventricular septum (57.1% vs. 25 The mean diameters of the pulmonary artery, and SVC, were significantly higher in adverse than in non-adverse outcome groups (P = 0.001 and 0.016) with an odds ratio of 1.33 (table 2 & 4). ROC curve revealed AUC for PA diameter = 0.747 (95% CI 0.620-0.873, p 0.001) with optimum cut off =29.5 mm (sensitivity 75%, specificity 71%) (table 3…”
Section: Other Ct Parametersmentioning
confidence: 95%